Clostridium polynesiense sp. nov., a new member of the human gut microbiota in French Polynesia. (December 2015) - Sankar, Senthil Alias; Rathored, Jaishriram; Metidji, Sarah; Lagier, Jean-Christophe; Khelaifia, Saber; Labas, Noemie; Musso, Didier; Raoult, Didier; Fournier, Pierre-Edouard
Abstract: Strain MS1, a Gram-positive, obligately anaerobic, motile and spore-forming rod belonging to the Clostridium genus, was isolated from the feces of a healthy Polynesian male living in French Polynesia. The temperature range for growth was 30–45 °C. We sequenced its complete genome and studied its phenotypic characteristics. The 3, 560, 738-bp long genome (one chromosome, no plasmid, G + C content 34%) contained 3535 protein-coding and 70 RNA genes. Strain MS1 exhibited a 98.24% 16S rRNA similarity with Clostridium amylolyticum, the phylogenetically closest species. When compared with other Clostridium species with standing in nomenclature, it had an average genomic similarity of 68.8–70%, a unique MALDI-TOF spectrum, and differed in nitrate reduction, motility andl -arabinose andd -lactose metabolism with most of the closest species. Therefore, strain MS1 is sufficiently distinct from type strains of the genus Clostridium to represent a novel species within this genus, for which the name Clostridium polynesiense sp. nov. is proposed. The type strain of C. polynesiense is MS1 T (= CSUR P630 = DSM 27072). Highlights: We describe Clostridium polynesiense strain sp. nov., a new Clostridium species. The type strain MS1 T was isolated from the fecal flora of a healthy Polynesian male. We sequenced its complete genome and studied its phenotypic characteristics. Strain MS1 T exhibited 69–70% average genomic similarities with Clostridium species. Strain MS1 T also differed phenotypically from the closest Clostridium species.